Evaluation of indole-based organometallics as transfer hydrogenation catalysts with anticancer activity - Rafols, Laia; Azmanova, Maria; Perrigault, Nathan; Cooper, Patricia A.; Shnyder, Steven D.; Martin, William H.C.; Pitto-Barry, Anaïs (Journal of organometallic chemistry, 2024)
•Neutral metal complexes with a S∩N indole ligand have been synthesised.•The metal ion (Ru, Os, Rh, Ir) influences the catalytic activity for NAD+ reduction.•In vivo studies reveal Rh complex exhibits the more selectivity.•The mechanism of action is based on ROS production. Half-sandwich complexes containing transition metals offer a wide range of applications owing to their interactions with a variety of targets/molecules that are not accessible for some organic scaffolds. The use of such complexes is therefore a way to provide new mechanisms of drug action. Here, we report a series of neutral metal complexes of the type [(arene)M(O-cyclohexyl-1H-indole-2-carbothiolate)Cl] that have the ability to reduce the coenzyme NAD+ at physiological conditions in the presence of sodium formate as an hydride donor. The influence of the metal ion (Ru, Os, Rh, Ir) is studied to establish some structure-activity relationships. The [(η6-p-cym)Ru(O-cyclohexyl-1H-indole-2-carbothioate)Cl] is the most active catalyst of this family of complexes with a turnover frequency (TOF) of 14.79 h-1 for the transfer hydrogenation reaction of NAD+ to give 1,4-NADH in the presence of formate. Further in vitro studies were carried out to determine a relationship between catalytic activity and potency as an anticancer drug, with the rhodium complex promisingly showing 7x more selectivity towards cancer cells (A2780) than normal cells (PNT2). Preliminary in vivo studies demonstrated the importance of co-treatment with formate to enhance activity. This work gives insights into the mechanism of action of this family of indole-based organometallic complexes. [Display omitted]